2021
DOI: 10.3390/pharmaceutics13071013
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Ex Vivo Animal Models to Test the Performance of Intravitreal Liposomal Drug Delivery Systems

Abstract: There is a strong need for innovative and efficient drug delivery systems for ocular therapy development. However, testing intravitreal drug delivery systems without using live animals is challenging. Ex vivo animal models offer an interesting alternative. We analyzed the potential of using fresh porcine eyes obtained from the local slaughterhouse as a model for testing the intravitreal biodistribution and retention of liposomes with or without polyethylene glycol (PEG) conjugation and with different surface c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…In the explant culture system, we do not preserve the vitreous after the culturing, so the IVT mobility of the pyruvate-liposomes was not tested. Previously we have documented the bio-distribution of similar liposomes and found that the retina could be reached after an IVT injection into ex vivo porcine eyes [40]. This is in line with similar studies [38, 41].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the explant culture system, we do not preserve the vitreous after the culturing, so the IVT mobility of the pyruvate-liposomes was not tested. Previously we have documented the bio-distribution of similar liposomes and found that the retina could be reached after an IVT injection into ex vivo porcine eyes [40]. This is in line with similar studies [38, 41].…”
Section: Discussionsupporting
confidence: 89%
“…This would make it easier to find a suitable dosing regimen and would allow for prolonged drug exposure in the target cell, minimizing administration frequency [42]. This in turn is especially relevant for IVT injections that carry a range of potential complications [40,[43][44][45].…”
Section: Pyruvate-liposomes For Clinical Usementioning
confidence: 99%
“…Hence, it can be concluded that U4T-12 NPs presented exceptional properties regarding their adherence and distribution towards the retinal tissue. Christensen et al showed that positively charged and PEG-coated liposomes could be retained at the retina for at least 24 h in ex vivo porcine eyes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the literature on LNPs for ocular permeability and retinal drug delivery is very limited. The team of Schipper and Paquet-Durand used LNCs to deliver CN03, a cGMP analogue, for the treatment of retinal degeneration, 55 but the drug permeation through the cornea proved to be too low for further clinical considerations. However, INV application of 2 mg mL À1 of fluorescently labeled LNCs (d = 48-72 nm, z = À0.3 to À11 mV) and liposomes showed promising improvements (Fig.…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%